2001
DOI: 10.1093/aje/153.6.572
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentrations of Carotenoids, Retinol, and Tocopherols in Preeclamptic and Normotensive Pregnant Women

Abstract: This case-control study was conducted in Lima, Peru, from June 1997 through January 1998 to assess whether plasma concentrations of carotenoids (alpha-carotene, beta-carotene, lycopene, lutein, zeaxanthin, beta-cryptoxanthin), retinol, and tocopherols (alpha-tocopherol and gamma-tocopherol) are decreased in women with preeclampsia. A total of 125 pregnant women with preeclampsia and 179 normotensive pregnant women were included. Plasma concentrations of antioxidants were determined using high performance liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 35 publications
6
56
0
Order By: Relevance
“…Decreased levels of b-carotene (Mikhail et al 1994;Palan et al 2001), lycopene (Palan et al 2001) and retinol (Zhang et al 2001) have been reported in women with pre-eclampsia, while another study has reported increased retinol levels (Williams et al 2003). Williams et al (2003), who sampled women in the early postpartum period, have also noted decreases in pre-eclampsia risk with increasing concentrations of a-carotene, b-carotene, b-cryptoxantin, lutein and zeaxantin, although such a relationship was not observed by Zhang et al (2001). Differences in study design, differences in population characteristics (such as maternal age, race or ethnicity), overall dietary intake habits, use of prenatal multivitamins and other nutritional supplements, and limited statistical power are likely to have contributed to the variability in results across studies.…”
Section: The Maternal Circulation and Oxidative Stressmentioning
confidence: 99%
“…Decreased levels of b-carotene (Mikhail et al 1994;Palan et al 2001), lycopene (Palan et al 2001) and retinol (Zhang et al 2001) have been reported in women with pre-eclampsia, while another study has reported increased retinol levels (Williams et al 2003). Williams et al (2003), who sampled women in the early postpartum period, have also noted decreases in pre-eclampsia risk with increasing concentrations of a-carotene, b-carotene, b-cryptoxantin, lutein and zeaxantin, although such a relationship was not observed by Zhang et al (2001). Differences in study design, differences in population characteristics (such as maternal age, race or ethnicity), overall dietary intake habits, use of prenatal multivitamins and other nutritional supplements, and limited statistical power are likely to have contributed to the variability in results across studies.…”
Section: The Maternal Circulation and Oxidative Stressmentioning
confidence: 99%
“…1 Despite extensive research, the aetiology of pre-eclampsia is still one of the major unsolved mysteries in obstetrics. It is widely accepted that endothelial cell dysfunction resulting in vascular permeability plays an important role in the pathophysiology of pre-eclampsia.…”
Section: Introductionmentioning
confidence: 99%
“…During pregnancy in humans, maternal blood volume increases 45-50%, and the vascular system must adapt to these increases in volume without dramatic changes in blood pressure. Either low or high maternal blood pressure during pregnancy can result in poor fetal outcomes in humans; however, systolic blood pressures in the SK3 T/T mice were similar to WT mice (16,29). A decreased peripheral vascular resistance in the SK3 T/T mice, as suspected from both uterine and mesenteric vessel changes, may decrease afterload of the heart, resulting in enhanced EF in these mice during pregnancy.…”
Section: E828 Sk3 Channels Induce Fetal Lossmentioning
confidence: 87%